Community-Led Tourism Transformation: Moving Beyond Sustainability in North Lombok - Ilham Zitri (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2025)
Sustainable tourism has become a dominant paradigm in regional development; however, its implementation often emphasizes economic growth and environmental preservation while overlooking community empowerment. North Lombok Regency, one of Indonesia’s leading tourism destinations, has experienced complex development dynamics following the 2018 earthquake and the COVID-19 pandemic. These conditions have necessitated a transformation toward a beyond sustainability approach through Community-Based Tourism (CBT), positioning local communities as key actors in tourism governance. This study aims to analyze policy directions, development strategies, and tourism performance achievements in North Lombok, and to assess the extent to which CBT principles have been implemented. A qualitative descriptive approach was employed, using policy documents (RENSTRA 2021–2026, RENJA 2022–2023, and LKJIP 2023) and tourism performance data. Data were analyzed using content analysis and network analysis to identify patterns of collaboration among stakeholders. The findings reveal a significant shift from growth-oriented tourism toward inclusive, community-led development. Tourism indicators show a 113% increase in visitor numbers, a 46% rise in regional tourism revenue, and expansion of active tourism villages. Network analysis indicates a moderately dense collaboration (density 0.62), with the Tourism Office and Pokdarwis Senaru as central actors. The study concludes that the beyond sustainability approach strengthens community resilience, promotes equitable development, and fosters participatory tourism governance.